The Problems of Practical Education Program's Application from Fourth Year Class Teacher Student's Viewpoint A Field Study In Education Faculty, Tartous University - Hmaydoush, Anwar; Aizouky, Maha (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research aimed to explore The Problems of Practical Education Program's Application from Fourth Year Class Teacher Student's Viewpoint in Education Faculty, Tartous University. The descriptive approach was adhered. So a special questionnaire consisted of (31) items in four fields (role of academic supervisor, practical education programs management, problems of student teacher and training school) was designed for that purpose, sample of this research was selected randomly and consisted of (80), The research's results showed existence of problems of Practical Education Program's Application from Fourth Year Class Teacher Student's Viewpoint. The problems related to practical education programs managementoccupied the firs position. The problems related to the training schoolranked second,and the problems related to the student's teacher ranked third, while the problems concerning the role of the academic supervisor occupiedthe fourthposition. Thisrecommendedthe need to develop the practical aspects of education program like theoretical content and linking it with practical one dramatically. Allocate sufficient period of time for each stage of the practical education. Solving the problems of student teacher as we can.Effective coordination with the schools training and provide them with suitable enough instructional media to make them eligible center for student teacher.